Double Sequence Space of Fuzzy Real Numbers Defined by Orlicz Function - Paudel, Gyan Prasad; Pahari, Narayan Prasad; Kumar, Sanjeev (The Nepali Mathematical Sciences Report, 2022)
The theory of fuzzy logic and the fuzzy set has been successfully applied in various fields of research in social science, management science, and mathematics. In this paper, we use the concept of Fuzzy real numbers to introduce and study the new double sequence spaces l∞ (M, λ, ρ), C F (M, λ, ρ) and CoF (M, λ, ρ) of fuzzy real numbers defined by the Orlicz function and study some of their properties like linear space structure, completeness, and solidness.